HUBUNGAN ANTARA AKTUALISASI DIRI DENGAN KEPERCAYAAN DIRI PADA KOMUNITAS TEATER - Chusnul Chotimah; Eko Hardiansyah (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
The problem in this study is low self-confidence among members of the theater community in East java with various categories such as nervousness, doubt, anxiety, lack of feeling in the process, lack of mastery of the stage when acting out a script, lack of knowledge about stage blocking, less able to build chemistry with the opponent playing the script. This study aims to find out the result of the relationship between self-actualization and self-confidence in theater communities in East Java. Confidence can lead to the belief that within a person has the ability. The research method uses correlational. Colleting data using a questionnaire with a population of 1700 members and respondents used as many as 289 members. Sampling used accidental sampling, wich was quted by Sugiyono (2019). The reliability test uses the Alpha Cronbach method with a standard > 0.9. the analysis technique uses simple linier regression with the help of JASP 0.16. the result of the study show that there is a positive and significant relationship to self-actualization with self-confidence getting a score of 73 %.